Evolutionarily divergent nidovirus with an exceptionally large genome identified in Pacific oysters undergoing mass mortality - Kevin Xu Zhong; Amy M. Chan; Kristina M. Miller; Rob Saunders; Curtis A. Suttle (Proceedings of the National Academy of Sciences, 2025)
Metatranscriptomic data from a mass-mortality event of adult Pacific Oysters, Crassostrea ( Magallana ) gigas , the most widely cultivated shellfish globally, revealed a nidovirus shown to replicate in a bivalve, Pacific Oyster Nidovirus 1 (PONV1). At 64,331 bp of linear bisegmented, positive-sense single-stranded RNA, PONV1 has one of the largest genomes reported for an RNA virus. Moreover, transcriptomic data reveal that many conspecific viruses of PONV1 occur in Pacific oysters from Europe and the Pacific coasts of Asia and North America. PONV1 (tentative species Megarnavirus gigas ) and its conspecific viruses represent a putative family, Megarnaviridae , that is widely divergent from other families of nidoviruses, and encodes protein domains likely involved in virus–host interaction that are undescribed for other nidoviruses. Given that PONV1 occurs in diseased Pacific oysters undergoing mass mortality, and that close relatives of PONV1 are widespread globally, it emphasizes the need for caution in the translocation of Pacific oyster spat that routinely occurs.